EAU RISK GROUPS APPLIED ON PATIENTS TREATED WITH RADICAL PROSTATECTOMY - ANALYSIS OF PATHOLOGY SPECIMENS AND PATIENT SURVIVAL - Boyan Lazarov (Peytchinski Publishing, 2024)
Purpose: The European Association of Urology (EAU) classifies patients with prostate cancer into three risk groups - low-risk, intermediate- and high-risk depending on the probability of biochemical progression after treatment with curative intent (either radical prostatectomy or radiotherapy). The aim of the present study is to analyze our experience with patients who underwent radical prostatectomy and to look for the relationship between the pathological results from the operation and the distribution of patients into risk groups. Material/Methods: A single-center, non-interventional study was conducted. The study was performed after analysis of patients undergoing radical prostatectomy (either open or laparoscopic) at the Clinic of Urology in St. Anna Hospital in Varna. The number of patients available for analysis was 201. Data were analyzed with IBM SPSS version 23. Results: We found that high-risk patients had unfavorable results from the examination of the pathology specimens- patients with pT3a and pT3b were more often from the high-risk group. High-risk patients were also at increased risk of PSA progression and development of distant metastases. Conclusions: The EAU-risk groups will probably undergo changes connected with the improved methods for the diagnosis of prostate cancer. But still, it is a valid tool which correctly predicts the unfavorable pathology of the removed specimen and also the risk of biochemical progression after radical prostatectomy.